Community-acquired bacterial meningitis in adults: in-hospital prognosis, long-term disability and determinants of outcome in a multicentre prospective cohort. (September 2020) - Tubiana, S.; Varon, E.; Biron, C.; Ploy, M.-C.; Mourvillier, B.; Taha, M.-K.; Revest, M.; Poyart, C.; Martin-Blondel, G.; Lecuit, M.; Cua, E.; Pasquet, B.; et al.
Abstract: Objectives: To identify factors associated with unfavourable in-hospital outcome (death or disability) in adults with community-acquired bacterial meningitis (CABM). Methods: In a prospective multicentre cohort study (COMBAT; February 2013 to July 2015), all consecutive cases of CABM in the 69 participating centres in France were enrolled and followed up for 12 months. Factors associated with unfavourable outcome were identified by logistic regression and long-term disability was analysed. Results: Among the 533 individuals enrolled, ( Streptococcus pneumoniae 53.8% (280/520 isolates identified), Neisseria meningitidis 21.3% (111/520), others 24.9% (129/520)), case fatality rate was 16.9% (90/533) and unfavourable outcome occurred in 45.0% (225/500). Factors independently associated with unfavourable outcome were: age >70 years (adjusted odds ratio (aOR) 4.64; 95% CI 1.93–11.15), male gender (aOR 2.11; 95% CI 1.25–3.57), chronic renal failure (aOR 6.65; 95% CI 1.57–28.12), purpura fulminans (aOR 4.37; 95% CI 1.38–13.81), localized neurological signs (aOR 3.72; 95% CI 2.29–6.05), disseminated intravascular coagulation (aOR 3.19; 95% CI 1.16–8.79), cerebrospinal fluid (CSF) white-cell count <1500 cells/μL (aOR 2.40; 95% CI 1.42–4.03), CSF glucose concentration (0.1–2.5 g/L: aOR 1.92; 95% CI 1.01–3.67; <0.1 g/L: aOR 2.24; 95% CI 1.01–4.97), elevated CSF protein concentration (aOR 1.09; 95% CI 1.03–1.17), time interval between hospitalization and lumbar puncture >1 day (aOR 2.94; 95% CI 1.32–6.54), and S. pneumoniae meningitis (aOR 4.99; 95% CI 1.98–12.56), or meningitis other than N. meningitidis (aOR 4.54; 95% CI 1.68–12.27). At 12 months, 26.7% (74/277) had hearing loss, 32.8% (87/265) depressive symptoms, 31.0% (86/277) persistent headache, and 53.4% had a physical health-related quality of life (142/266) <25th centile of the distribution of the score in the general French population (p < 0.0001). Conclusions: The burden of CABM (death, disability, depression, impaired quality of life and hearing loss) is high. Identification of cases from the first symptoms may improve prognosis. ClinicalTrial: Gov identification number: NCT01730690.